Squamata, Serpentes, Dipsadidae, Philodryas viridissima (Linnaeus, 1758): First record in the state of Acre, northern Brazil - Marco Freitas; Daniella França; Paulo Bernarde (Check List, 2012)
The common green racer Philodryas viridissima (Linnaeus, 1758) is an arboreal and terrestrial snake species broadly distributed in southern Venezuela, Colombia, Ecuador, Peru, Bolivia, Guiana, Suriname, French Guiana, Paraguay up to Argentina, and most of Brazil. In this study, we report the first record of P. viridissima in the state of Acre, Brazil, in the Chico Mendes Extractive Reserve. This record expands the species distribution in 280 km to the southwest of Boca do Acre, state of Amazonas, which was the nearest record of this species in Brazilian Amazon until now.